الاستراتيجية التدريبية كآلية للتقليل من الضغوط المهنية لدى الموظفين – دراسة حالة جامعة عباس لغرور خنشلة- - أ.مانع, سبــــــرينة (Recherches économiques et managériales, 2014)
الملخص:    في إطار معالجة مشكلة ضغوط العمل لدى الموظفين ودور الاستراتيجية التدريبية في التقليل منها، قامت الباحثة بدراسة حالة جامعة عباس لغرور "خنشلة"، حيث كان عدد الموظفين الإداريين فيها 304 موظفا إداريا، بالتالي تم اعتماد عينة المسح الشامل. وقد اعتمدت الباحثة في جمع البيانات على الاستمارة (الاستبيان)، حيث تم توزيع 304 استمارة استرجع منها 265 واستبعد 5 فكان عدد الاستمارات القابلة للتحليل الإحصائي 260 استمارة، كما اعتمدت الباحثة برنامج spss في التحليل الإحصائي. من أهم النتائج التي توصلت إليها الدراسة أن الاستراتيجية التدريبية تشكل آلية هامة للتقليل من ضغوط العمل لدى الموظفين في الجامعة محل الدراسة، لكن هناك بعض العوامل التي تقلل من فاعليتها نذكر: روتينية العمل في الجامعة محل الدراسة يشكل مصدرا لضغوط العمل لدى الموظفين، عدم إتاحة الفرص للموظفين لإظهار إمكانياتهم الوظيفية واستغلالها يشكل مصدرا لضغوط العمل لديهم، عدم مقارنة أداء الموظفين المتدربين قبل وبعد العملية التدريبية وتقييمه لتحديد مدى فعالية البرامج التدريبية يؤثر على فعالية الاستراتيجية التدريبية، كما أن الجامعة لا تولي اهتماما بتقصي أراء الموظفين المتدربين حول مدى رضاهم واستفادتهم من البرامج التدريبية، كما لا تولي اهتماما بالتحديد الجيد للبرامج التدريبية وبالتالي غياب التغطية الجيدة للاحتياجات التدريبية، هذا يقلل من فعالية الاستراتيجية التدريبية في التقليل والحد من ضغوط العمل لدى الموظفين. Abstract :     For studying professional pressure on university administrative workers and the role of Training Strategy in reducing it, the researcher studied the case of Abbas Leghrour University at Khenchela, where a sample survey was conducted to 304. The researcher has adopted the form (questionnaire) to collect data. Where it is distributed to 304 administrative workers, among them 265 questionnaires are recovered and 05 are canceled. Consequently, the number of forms susceptive to analysis is 260 forms. Moreover, the software SPSS has been applied in the statistical analysis.      As a result, this study finds that Training Strategy is an important mechanism to reduce the professional pressure on university workers under study. However, there are some factors, which reduce the effectiveness of training strategy such as: first, routine of the work at the university that causes stress among employees. Second, Lack of opportunities for employees to show their potential training strategy and talents. Third, the absence of evaluating the performance of trained employee before and after the training process may not show the effectiveness of training programs. Besides, the university does not pay attention to investigate the opinions of trained workers about how are they satisfied and benefit from training programs, it also does not identify training programs well.      Thus, the university does not pay attention specifically for training programs and therefore the absence of good coverage of training needs, which reduce the effectiveness of training programs to diminish work stress among administrative workers.